2019
DOI: 10.1016/j.chempr.2018.09.026
|View full text |Cite|
|
Sign up to set email alerts
|

Charge Transfer between [4Fe4S] Proteins and DNA Is Unidirectional: Implications for Biomolecular Signaling

Abstract: Understanding molecular signaling mechanisms in cells is critically important to biology and medicine. A prominent case is the search for drug targets in cancer signaling pathways. Recently, it was proposed that charge transfer through DNA may enable signaling between iron-sulfur proteins involved in DNA repair and replication. We show that exclusive DNA mediation is energetically unfavorable and kinetically unfeasible, but redox agents might assist the protein signaling. Our analysis narrows the range of poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
56
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(63 citation statements)
references
References 61 publications
2
56
0
Order By: Relevance
“…In a previous study, we showed that through-protein HT from an oxidized system (a nucleic acid double strand) to highpotential [4Fe4S] clusters may generally occur on a millisecond to microsecond timescale (17). This theoretical result agrees with previous experimental findings on the viability of redox signaling involving [4Fe4S] proteins relevant to DNA replication and repair (18,30).…”
Section: G829-m713-w55-w531-[4fe4s]supporting
confidence: 89%
See 2 more Smart Citations
“…In a previous study, we showed that through-protein HT from an oxidized system (a nucleic acid double strand) to highpotential [4Fe4S] clusters may generally occur on a millisecond to microsecond timescale (17). This theoretical result agrees with previous experimental findings on the viability of redox signaling involving [4Fe4S] proteins relevant to DNA replication and repair (18,30).…”
Section: G829-m713-w55-w531-[4fe4s]supporting
confidence: 89%
“…We tested the EHPath code by replicating the hopping pathways and mean residence times identified in earlier analysis (see Table 1 of ref. 17). The computations also identified weaker hole hopping routes that can be accessed on biologically relevant timescales, highlighting the capability of EHPath to map charge hopping routes in proteins.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…In this issue of Chem, Migliore and co-workers set out to answer this debate by performing a theoretical study of charge transfer in this system to determine whether charge transfer between [4Fe4S] clusters and DNA/ RNA is thermodynamically and kinetically possible. 6 Therefore, this is an excellent use of applied theoretical chemistry to answer a complex biological question. The experimental evidence is contradictory, and the experiments themselves are complicated and debated.…”
mentioning
confidence: 99%
“…Reprinted from Migliore and co-workers. 6 excess electron transfer from an anionic nucleic acid to an oxidized [4Fe4S] 3+ cluster can occur. However, now the excess electron transfer from a reduced [4Fe4S] 2+ cluster in p180c to the duplex is energetically unfavorable.…”
mentioning
confidence: 99%